2022
DOI: 10.1039/d2ta06141d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced solar water splitting of BiVO4photoanodes byin situsurface band edge modulation

Abstract: Photoinduced charge separation and transfer have been recognized as the one of the core factors affecting the photoelectrochemical (PEC) performance of BiVO4 based photoanodes. To achieve a higher charge separation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Song and co‐workers used a gas‐phase cation exchange (CA) method to in situ modulate the surface band edge of the BiVO 4 photoanode by partially replacing Bi on the surface with V to form a V‐rich surface. The charge separation efficiency of the optimized BiVO 4 /BiVO 4 −V Bi photoanode was significantly enhanced from 56.5 % to 81.5 % compared to pristine BiVO 4 [10] …”
Section: Bivo4 Interface Heterojunctionmentioning
confidence: 93%
See 1 more Smart Citation
“…Song and co‐workers used a gas‐phase cation exchange (CA) method to in situ modulate the surface band edge of the BiVO 4 photoanode by partially replacing Bi on the surface with V to form a V‐rich surface. The charge separation efficiency of the optimized BiVO 4 /BiVO 4 −V Bi photoanode was significantly enhanced from 56.5 % to 81.5 % compared to pristine BiVO 4 [10] …”
Section: Bivo4 Interface Heterojunctionmentioning
confidence: 93%
“…The charge separation efficiency of the optimized BiVO 4 /BiVO 4 À V Bi photoanode was significantly enhanced from 56.5 % to 81.5 % compared to pristine BiVO 4 . [10] C 3 N 4 is modified by doping Boron (B) and Phosphorus (P) to match the energy band and Fermi energy level of BiVO 4 , so as to construct heterojunction. Zeng et al combined Mo : BiVO 4 and C 3 N 4 to form a heterojunction, it was found that the interface between C 3 N 4 and Mo : BiVO 4 would form a photoinduced carrier recombination center due to the mismatch between their energy bands and Fermi levels.…”
Section: Type I/type II Heterojunctionmentioning
confidence: 99%
“…18 However, we demonstrate that judicious application of a metal oxide coating can preserve the electronic structure, resulting in an effective semiconductor-coating-liquid junction. 22,23 Effective oxygen evolution reaction (OER) photocatalytic materials require a band gap energy in the visible range and the application of surface coatings that serve multiple functions, including modifying the semiconductor surface to promote catalytic acceleration of OER kinetics. 24 In these approaches, the introduction of cocatalysts is an effective strategy to enhance PEC performance, owing to their advantages of low overpotential and good stability, as well as their ability to efficiently capture accumulated holes on the surface of the photoelectrode for water oxidation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…WBGSMs, owing to their unique properties, i.e., the combination of high optical transparency in the visible spectrum and electronic conductivity, play an important role in modern optoelectronic applications. [1][2][3][4] The growing demands in the optoelectronic field, such as flat panel displays, 5,6 smart windows, 7 solar cells, [8][9][10][11][12][13][14] etc., give rise to high consumption of excellent WBGSMs, especially indium (In)-containing WBGSMs, for example, Sn-doped In 2 O 3 (ITO) 15 and InGaZnO alloys (IGZO). 16 However, the restricted availability of natural resources such as In leads to the high cost of the fabricating devices.…”
Section: Introductionmentioning
confidence: 99%